Characterization of Cerebral Glutamine Uptake from Blood in the Mouse Brain: Implications for Metabolic Modeling of 13C NMR Data. Issue 10 (October 2014) - Bagga, Puneet; Behar, Kevin L; Mason, Graeme F; De Feyter, Henk M; Rothman, Douglas L; Patel, Anant B
13 C Nuclear Magnetic Resonance (NMR) studies of rodent and human brain using [1- 13 C]/[1, 6- 13 C2 ]glucose as labeled substrate have consistently found a lower enrichment (~25% to 30%) of glutamine-C4 compared with glutamate-C4 at isotopic steady state. The source of this isotope dilution has not been established experimentally but may potentially arise either from blood/brain exchange of glutamine or from metabolism of unlabeled substrates in astrocytes, where glutamine synthesis occurs. In this study, the contribution of the former was evaluated ex vivo using 1 H-[ 13 C]-NMR spectroscopy together with intravenous infusion of [U- 13 C5 ]glutamine for 3, 15, 30, and 60 minutes in mice. 13 C labeling of brain glutamine was found to be saturated at plasma glutamine levels > 1.0 mmol/L. Fitting a blood–astrocyte–neuron metabolic model to the 13 C enrichment time courses of glutamate and glutamine yielded the value of glutamine influx, V Gln(in), 0.036 ± 0.002 μ mol/g per minute for plasma glutamine of 1.8 mmol/L. For physiologic plasma glutamine level (~0.6 mmol/L), V Gln(in) would be ~0.010 μ mol/g per minute, which corresponds to ~6% of the glutamine synthesis rate and rises to ~11% for saturating blood glutamine concentrations. Thus, glutamine influx from blood contributes at most ~20% to the dilution of astroglial glutamine-C4 consistently seen in metabolic studies using [1- 13 C]glucose.